Identifying Pronunciation Errors in English Among Postgraduate Students: A Phonetical Perspective - FARTIZAN, Siti; ABDUH, Amirullah; SAMSIDAR, Samsidar (Research and Innovation in Applied Linguistics, 2024)
This research aims to address two primary problem statements: first, to identify the types of English pronunciation errors made by third-semester students in the postgraduate English language education program; and second, to determine the sources of these pronunciation errors among the same cohort of students. This research used a combination of phonetic and quantitative error analysis to identify the pronunciation errors among postgraduate students. The results showed that there were 16.16% of omission errors, 11.97% addition errors, 71.85% of word formation errors, and students 0% of word ordering error. For the sources of errors in the pronunciation of all students during the proposal seminar, researcher found that there was incomplete application of rule is source from omission errors such as letter /g/, /ʃ/, /dʒ/, /ə/, /ɪ/, /ɑː/, /t/, and /h/. The next source of errors false concepts hypothesized is source from addition errors such as letter /ɒ/, /ʌ/, /s/, /g/, /e/, /ɑː/, /u/, /w/, /a/, /j/, and /r/. There is also overgeneralization is source from misformation errors such as letter /aʊ/, /ɔː/, /h/, /ʒ, etc. Meanwhile for ignorance of rule restriction is source from misodering errors all students for misodering did not make that mistake.